Trade finance in periods of crisis: What have we learned in recent years? - Marc Auboin; Martina Engemann (World Trade Organization (WTO), 2013)
This paper reviews a number of initiatives taken by public and private institutions aimed at minimizing the impact of the on-going crisis of the financial sector on its ability to supply trade finance to support trade at affordable rates. In doing so, it draws a few policy lessons. One of them is that a relatively stable segment of the financial industry is now regularly hit by the contagion of financial crises, with potentially very harmful spill-overs on global trade through a dry up of its financing. Specific policy measures to restore confidence in this otherwise safe market required a good level of coherence and dialogue between national governments and international and regional development organizations. Lessons from the Asian and Latin American financial crises of the late 1990's have been learned and academia provided input by developing understanding on a previously under-rated topic in the literature. Learning-by-doing and leadership have also been features of the policy response, which altogether had some successes. Still, longer-term challenges remain, such as addressing the structural gaps in the availability of trade finance in low-income countries - ad hoc programs have been designed to fill the gap between the perceived and actual risk of extending trade credit to traders in these countries. Moreover, regulation of the trade finance market needs to continue to take into account its low-risk character, the absence of leverage and its impact on development.
Keywords: F13; F34; F36; O19; G21; G32; 330; cooperation with international financial institutions; coherence; G-20; financial crisis; Außenhandelsfinanzierung; Finanzsektor; Internationale Finanzierung; Außenhandelsfinanzierung; Internationale Finanzierung; Finanzkrise